Vol.2 - Tisdell, Clem (ed.) (New Delhi, 2005)
In recent decades, the process of globalisation has gathered momentum. In turn, this has necessitated economic policy responses by governments throughout the world, and these have further accelerated economic globalisation and have magnified other dimensions of growing globalisation, such as cultural change. This distinguished contributors to this book (drawn from all regions of the world) provide assessments of globalisation from varied perspectives, and outline and evaluate policy responses by governments from all major regions of the world, both by those of developed nations and by those of less developed countries. Thus, this book provides a wide coverage and a variety of views about the consequences and the ways in which individual nations and groups of nations have endeavoured to cope with globalisation.
Keywords: Globalisation